KEMAMPUAN MEMBAYAR IURAN JAMINAN KESEHATAN NASIONAL PESERTA PENERIMA BANTUAN IURAN (JKN PBI) KOTA TANGERANG TAHUN 2023 - Darwati, Darwati; Pujiyanto, Pujiyanto; Hidayat, Budi (UI Scholars Hub, 2023)
The number of National Health Insurance (JKN) participants receiving Contribution Assistance (PBI) in Tangerang City from regional funding continues to increase by around 8.85% per year. On the other hand, the number of JKN participants who are non-wage earners (PBPU) and non-workers (BP) who pay contributions independently has decreased by around 0.7% per year from 2017-2022. One of the implications of this phenomenon is that the regional budget to finance JKN contributions for PBI participants is much larger than the budget for other programs. In 2020, JKN contribution payments for Tangerang City APBD PBI participants amounted to 57.81%, in 2021 it amounted to 75.32%, and in 2022 it amounted to 77.09% of the total Tangerang City Health Service budget excluding personnel expenditure and government governance. The research aims to analyze the ability to pay JKN contributions for the people of Tangerang City in 2023 and the influencing variables. The research used a cross-sectional design with a sample of 400 JKN PBI segment participants who had been selected by accident. Data was collected at two hospitals in the Tangerang City area in June 2023 using a questionnaire instrument. The average ability to pay JKN contributions is IDR 54,904/person/month. As many as 61.25% of respondents have the ability to pay JKN contributions of IDR 35,000/person/month. There is potential for savings in Tangerang City APBD expenditure of IDR 92.7 billion/year if 61.25% of JKN PBI APBD participants who have the ability to pay IDR 35,000/person/month are excluded from PBI membership. The results of the multivariate analysis found that the dominant variable influencing the ability to pay JKN contributions was non-food expenditure.